Identifying the effect of the hydrated lime on self-healing steel slag stone mastic asphalt using the induction heating method in tropical conditions - Irawati, Irawati; Djakfar, Ludfi; Arifin, Muhammad Zainul; Sabarudin, Akhmad; Dewi, Ilanka Cahya; Palgunadi, Irawan (Eastern-European Journal of Enterprise Technologies, 2025)
This study examines the effect of a hydrated lime additive on steel slag stone mastic asphalt for induction heating and induced healing applications. It evaluates the self-healing capabilities of hydrated lime-modified steel slag stone mastic asphalt under tropical conditions. The three-point bending was first tested on the steel slag-stone mastic asphalt mixture modified with hydrated lime (1 %, 2 %, 3 %, and 4 % by mix weight). The mix's fracture, displacement, cracking resistance, and flexibility index are evaluated. Subsequently, the fracture, displacement, cracking resistance, flexibility index recovery, and healing ratio for damage-healing were investigated. The research employs induction heating, which regulates temperature according to natural tropical conditions. The healing process is compared between heating in a tropical environment and heating with additional temperature. The results demonstrated that adding hydrated lime to steel slag stone mastic asphalt increased fracture strength, however, this improvement was accompanied by decreased displacement, cracking resistance, and flexibility. The findings indicate that the healing ratio of steel slag stone mastic asphalt is enhanced by 1 % hydrated lime. Adding 1 % hydrated lime is optimal for improving fracture strength and healing ratio. The fracture strength increased by 5 % with a 1 % variation of hydrated lime. The healing ratio of the 1 % hydrated lime-modified stone mastic asphalt increased by 14.57 % under natural conditions compared to 0 % hydrated lime steel slag stone mastic asphalt. Furthermore, the healing ratio of steel slag mastic asphalt with 1 % hydrated lime subjected to artificial heating increased by 22.08 % compared to stone mastic asphalt with 0 % hydrated lime under natural heating